Global Model of Intelligence and Memorizing of Information - Vidučić, Vinko (2009)
The object of analysis of this paper is information model of intelligence and memorizing from conception until a child starts to walk for the period from 2009 until 2020. In order to define main characteristics and determinants, the model of growth was used. The goal of the the evaluation and analysis of relevant variables and resulting rates of growth was to scientifically formulate the results of a research of a synergic relation between intelligence and information memorizing. Numerous adequate scientific methods were used, the most important among them: analysis and synthesis method, inductive and deductive method, descriptive method, comparative method, statistical and mathematical method, modelling method (matrix of growth), proving and disproving method. The main scientific hypothesis is confirmed through direct rates of growth of the model variables. In such a way the scientifically based confirmation of the hypothesis is provided. Namely, it is confirmed that, based on scientific comprehension about synergic relation between intelligence and information memorizing, it is possible to suggest a new „Information model of intelligence and memorizing from conception until a child starts to walk for the period from 2009 until 2020“.